As tensões territoriais ribeirinhas na reserva extrativista médio Juruá (AM) - Araújo, Nelcioney José de Souza (2009)
This study examines the territorial riverine tensions inside the extractive reserve. We start from the classic analyses concerning the territory and territoriality, trying to understand how they materialize the territorialities and when they are used. The unit of empirical establishment is the extractive reserve of the Medium Juruá, located in the basin of the Juruá river and created in 1997 as a consequence of the rubber workers fight. Approximately 1955 of people live inside this conservation unit, on which has influence the norms, the management and the monitoring imposed by the model. We try to cover the environmental politics procedures around the creation of conservation units in Brazil and, specially, the state of Amazon as preservation strategy. Alongside we reflect on the involved actors performance and the consequences for the populations from the reserve. We illustrate this performance demonstrating, by means of the participant comment, as each community deals with the model and which the repercussions, taking into account that the riverine people are lethargic by the commercial point of view and that the environmental agency and the Association that represents them doesn t have yet a plan of development nor perspective to brighten up this situation, that generates tensions. Therefore, the observed territorial tensions in the reserve are configured as one of the main problems faced the by model.